Handbook of molecularly imprinted polymers - Alvarez-Lorenzo, Carmen; Concheiro, Angel (Shrewsbury : iSmithers Rapra Publishing, 2013)
This handbook provides a useful guide to preparing molecularly imprinted polymers (MIPs) for diverse practical applications. The first chapter covers the general aspects of molecular imprinting technology. The following chapters focus on specific applications, such as MIPs for sample concentration, MIPs for chromatography and related techniques, MIPs as sensor components, MIPs as traps for medical and bioremediation, MIPs as catalysts and artificial enzymes, and MIPs as components of drug delivery systems. All chapters of the handbook follow a common structure: interest of the MIP approach fo.
3.2.3.2 Precipitation Polymerisation3.2.3.3 Suspension Polymerisation; 3.2.3.4 Multistep Swelling Polymerisation; 3.2.3.5 Core-shell Polymerisation; 3.2.3.6 Sol-gel Polymerisation; 3.2.3.7 Grafting Polymerisation; 3.2.3.8 In situ Polymerisation; 3.3 General Recipes; 3.3.1 Molecularly Imprinted Solid-phase Extraction; 3.3.1.1 Materials Based on Magnetic Nanoparticle Composites; 3.3.1.2 Core-shell Silica Nanoparticles; 3.3.1.3 Multiwalled Carbon Nanotubes; 3.3.1.4 Monoliths; 3.3.1.5 Sol-gel Polymers; 3.3.2 Molecularly Imprinted Microextraction by Packed Sorbent
Description based upon print version of record.
Includes bibliographical references and index.
3.3.3 Molecularly Imprinted Polymers for Matrix Solid-phase Dispersion
Keywords: Molecular imprinting; Imprinted polymers; SCIENCE / Chemistry / Industrial & Technical; TECHNOLOGY & ENGINEERING / Chemical & Biochemical; Electronic books